2000
DOI: 10.1097/00000374-200009000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Objective Diagnosis of Alcohol Abuse: Compared Values of Carbohydrate-Deficient Transferrin (CDT), ??-Glutamyl Transferase (GGT), and Mean Corpuscular Volume (MCV)

Abstract: Carbohydrate-deficient transferrin proves to be the best marker of alcohol abuse. It allows objective detection so that therapeutic action can be started early, which is easier and more effective than in alcohol dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 43 publications
(30 reference statements)
2
17
0
1
Order By: Relevance
“…AST provided almost no discriminating power. MCV had a high specificity but a low sensitivity (Table 4), as described previously (20 ).…”
Section: Discussionsupporting
confidence: 66%
“…AST provided almost no discriminating power. MCV had a high specificity but a low sensitivity (Table 4), as described previously (20 ).…”
Section: Discussionsupporting
confidence: 66%
“…M ANY PAPERS HAVE reported on the performance of carbohydrate deficient transferrin (CDT) or gamma glutamyltransferase (GGT) as markers of excessive alcohol consumption (Allen et al, 1994;Mundle et al, 2000;Reynaud et al, 2000). These markers are potentially important for both the detection and monitoring of patients with alcohol dependence and for the early detection of nondependent hazardous or harmful drinking.…”
mentioning
confidence: 99%
“…Overload Screening (HEIRS) Study, Paul C. Adams, 1* David M. Reboussin, 2 Cathie Leiendecker-Foster, 3 Godfrey C. Moses, 4 Gordon D. McLaren, 5 Christine E. McLaren, 6 Fitzroy W. Dawkins, 7 Ishmael Kasvosve, 7 Ron T. Acton, 8 James C. Barton, 9 Dan Zaccaro, 2 Emily L. Harris, 10 Richard Press, 11 Henry Chang, 12 and John H. The diagnosis of hemochromatosis was previously based on a combination of clinical and laboratory assessments that included history and physical examination, increased transferrin saturation (TS) and serum ferritin, liver biopsy, the amount of iron removed by phlebotomy, and pedigree studies identifying other family members with iron overload (1 ). Since the discovery of the hemochromatosis gene (HFE) in 1996 (2 ), most studies from referral centers have shown that Ͼ90% of typical hemochromatosis patients are homozygous for the C282Y mutation of the HFE gene (3 ).…”
Section: Comparison Of the Unsaturated Iron-binding Capacity With Tramentioning
confidence: 99%
“…The use of biological markers such as CDT is of particular interest for identifying young heavy drinkers because other clinical signs of heavy drinking are generally absent and heavy drinking is a leading cause of morbidity and mortality in this age group (3,4 ). Several authors have shown interest in the ability of CDT to identify nondependent heavy drinkers (5,6 ); we therefore describe here the performance of CZE measurements of asialo-and disialo-Tf and TIA analysis of CDT in a large community sample of 19-year-old men, of whom 21% were heavy drinkers.…”
mentioning
confidence: 99%